The relationship between perceived peer support and academic adjustment among higher vocational college students: the chain mediating effects of academic hope and professional identity - Zhu, Yaoxiu; Lu, Haidong; Wang, Xinbo; Ma, Wenling; Xu, Min (Frontiers in Psychology, 2025)
PurposeAcademic adjustment is essential for the academic success of higher vocational college students. Although previous research has explored the role of perceived peer support in the academic adjustment of general undergraduate students, its role and underlying mechanisms in this group remain unclear. This study aims to explore the relationship between perceived peer support and academic adjustment, focusing on the chain mediating roles of academic hope and professional identity.MethodsA cross-sectional survey was conducted among 9,075 students from 35 higher vocational colleges across 15 provinces and cities in China, using multi-stage stratified random sampling. Validated scales were used to measure perceived peer support, academic adjustment, academic hope, and professional identity.ResultsThe findings revealed that perceived peer support not only directly influences academic adjustment but also exerts an indirect effect through the individual mediation of academic hope and professional identity, as well as through the sequential mediation from academic hope to professional identity.ConclusionPerceived peer support, academic hope, and professional identity significantly promote academic adjustment among higher vocational college students. These findings provide theoretical insights into the mechanisms of academic adjustment and offer practical implications for educational strategies, emphasizing the importance of fostering perceived peer support, academic hope, and professional identity to enhance students’ academic success.